Body Awareness and Bodily Dissociation Among Those With and Without Sexual Difficulties: Differentiation Using the Scale of Body Connection. Issue 8 (17th November 2017) - Carvalheira, Ana; Price, Cynthia; Neves, Cide F.
Abstract : The goal of this study was to explore potential body awareness and bodily dissociation differences between men and women with and without sexual difficulties, using the Scale of Body Connection in a sample of 909 participants. In women, bodily dissociation scores were significantly higher across all reported sexual difficulties, except in sexual pain. Women with lack of sexual interest and sexual arousal had significantly lower body awareness when compared to women without these difficulties. These findings suggest the importance of targeting body awareness and bodily dissociation in the treatment of women's sexual difficulties.